EXAMINING THE EFFECT OF TRANSPORT INFRASTRUCTURE ON ATTRACTING FOREIGN DIRECT INVESTMENT - Eyup Atioğlu; Osman Nuri Şahin (Hitit Sosyal Bilimler Dergisi, 2022)
Many factors play a role in determining the level of development in countries, and one of the main factors is FDI. To attract foreign capital to the country, it is necessary to realize the developments desired by the foreign capital and to pave the way for investments. The strong transportation infrastructure contributes to the development of the country not only in economic terms but also in many social and cultural aspects. With all these contributions, the benefits of transportation infrastructure investments make countries attractive for foreign capital. In this study, the relationship between investments in transportation infrastructure and foreign direct investments (FDI) was examined using the Arellano-Bond difference Generalized Method of Moments (GMM). The data set of the study covers the period between 2010 and 2017, and the analysis was carried out using data from 30 OECD countries. According to the findings, it has been determined that total transportation infrastructure investment expenditures positively affect foreign direct investments.